2018
DOI: 10.18632/oncotarget.24710
|View full text |Cite
|
Sign up to set email alerts
|

Combination of interferon-expressing oncolytic adenovirus with chemotherapy and radiation is highly synergistic in hamster model of pancreatic cancer

Abstract: Recent clinical trials utilizing Interferon-alpha (IFN) in combination with chemoradiation have demonstrated significant improvements in the survival of patients with pancreatic cancer. However, efficacy was limited by the systemic toxicity of IFN and low intratumoral levels of the cytokine. We sought to address these drawbacks by using an Oncolytic Adenovirus expressing IFN (OAd-hamIFN) in combination with chemotherapy and/or radiation in regimens mimicking the IFN-based therapies used in clinical trials. IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…Hemminki et al and others further demonstrated its effectiveness in patients who had failed conventional chemotherapy and radiation [156][157][158][159][160]170,171]. Similar to GMCSF, several other receptors and cytokines such as CD40L [162][163][164] and interferons [165][166][167][172][173][174] have also been evaluated. Yamamoto's group has effectively used interferon expressing OAdVs to target pancreatic cancer in mice models and immunocompetent hamster models [172][173][174].…”
Section: Protein-based Effectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemminki et al and others further demonstrated its effectiveness in patients who had failed conventional chemotherapy and radiation [156][157][158][159][160]170,171]. Similar to GMCSF, several other receptors and cytokines such as CD40L [162][163][164] and interferons [165][166][167][172][173][174] have also been evaluated. Yamamoto's group has effectively used interferon expressing OAdVs to target pancreatic cancer in mice models and immunocompetent hamster models [172][173][174].…”
Section: Protein-based Effectorsmentioning
confidence: 99%
“…Similar to GMCSF, several other receptors and cytokines such as CD40L [162][163][164] and interferons [165][166][167][172][173][174] have also been evaluated. Yamamoto's group has effectively used interferon expressing OAdVs to target pancreatic cancer in mice models and immunocompetent hamster models [172][173][174]. OAdVs have also been developed to express a monoclonal antibody against CTLA4.…”
Section: Protein-based Effectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for using Type-I IFN as a transgene in oncolytic viruses is that, apart from their antiviral function, they also have antitumor potential due to their role in the maturation of dendritic cells [75] and cytotoxic T cells [76]. An oncolytic adenovirus armed with IFN-α and used in combination with radiation was found to yield a modest increase in antitumor efficacy in murine models of pancreatic cancer [77]. Likewise, some degree of improvement in antitumor efficacy of oncolytic VACV [78], VSV [79], NDV [80] and measles [81] were observed after arming them with IFN-β.…”
Section: Interferonsmentioning
confidence: 99%
“…Hamsters are important animal models for studying various infectious diseases of humans [1][2][3][4][5][6][7][8]. The hamster models of pancreatic and oral cancer have gained importance in their respective fields [9][10][11][12][13][14]. Moreover, these animals have also been instrumental in studying metabolic and/or inflammatory diseases like diabetes and pancreatitis [15,16].…”
Section: Introductionmentioning
confidence: 99%